Blinded independent central reviews: The FDA weighs in. (18th July 2013) - Walovitch, Richard C.
Abstract: The FDA has recently issued a draft Guidance Standard for Clinical Trial Imaging Endpoints, which focuses on how to perform registration trials with imaging as an end-point or using imaging to determine patient eligibility. Leading up to the release of the guidance document, a major question was how the FDA viewed the value proposition of a blinded independent central review (BICR) of imaging data. The FDA states that a BICR is recommended in situations where clinical site image interpretation is variable and results of image measurements are important for eligibility determination, safety and/or efficacy end-points. This recommendation is based on the agency's assertion that the centralized process can better provide verifiable and uniform reader training, as well as ongoing management of reader performance, ensuring that the process is accurate and that bias and variability are minimized. In addition to a review of the guidance document, this article will discuss a decision tree algorithm for determining when and what type of BICR should be performed, the relationship between bias (accuracy), variability and blinding paradigms, along with criteria for using BICRs to interpret non-imaging subjective clinical trial data.